Sarcoplasmic reticulum calcium ATPase is inhibited by organic vanadium coordination compounds: pyridine-2-6-dicarboxylatodioxovanadium(V), BMOV and an amavadine analogue - Aureliano, M. (2012)
The general affinity of the sarcoplasmic reticulum (SR) Ca2+-ATPase was examined for three different classes of vanadium coordination complexes including a vanadium(V) compound, pyridine-2,6-dicarboxylatodioxovanadium(V) (PDC-V(V)), and two vanadium(IV) compounds, bis(maltolato)oxovanadium(IV) (BMOV), and an analogue of amavadine, bis(N-hydroxylamidoiminodiacetato)vanadium(IV) (HAIDA-V(IV)). The ability of vanadate to act either as a phosphate analogue or as a transition-state analogue with enzymes’ catalysis phosphoryl group transfer suggests that vanadium coordination compounds may reveal mechanistic preferences in these classes of enzymes. Two of these compounds investigated, PDC-V(V) and BMOV, were hydrolytically and oxidatively reactive at neutral pH, and one, HAIDA-V(IV), does not hydrolyze, oxidize, or otherwise decompose to a measurable extent during the enzyme assay. The SR Ca2+-ATPase was inhibited by all three of these complexes. The relative order of inhibition was PDC-V(V) > BMOV > vanadate > HAIDA-V(IV), and the IC50 values were 25, 40, 80, and 325 μM, respectively. Because the observed inhibition is more potent for PDC-V(V) and BMOV than that of oxovanadates, the inhibition cannot be explained by oxovanadate formation during enzyme assays. Furthermore, the hydrolytically and redox stable amavadine analogue HAIDA-V(IV) inhibited the Ca2+-ATPase less than oxovanadates. To gauge the importance of the lipid environment, studies of oxidized BMOV in microemulsions were performed and showed that this system remained in the aqueous pool even though PDC-V(V) is able to penetrate lipid interfaces. These findings suggest that the hydrolytic properties of these complexes may be important in the inhibition of the calcium pump. Our results show that two simple coordination complexes with known insulin enhancing effects can invoke a response in calcium homeostasis and the regulation of muscle contraction through the SR Ca2+-ATPase.